Analisis Pendapatan Usahatani Cabai Rawit Di Desa Tambelang Kecamatan Maesaan Kabupaten Minahasa Selatan - Mumu, Waraney Fichrates; Kapantow, Gene H.M.; Lumingkewas, Jelly Ribka Danaly (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the income of cayenne pepper farming in Tambelang Village, Maesaan District, South Minahasa Regency. This research was conducted for 2 months, from August to September 2022. The data collection method used in this research is the documentation method, which is a method that aims to obtain data related to research variables through various sources of literature and institutions. The data analysis method used in this study is to use descriptive analysis. The data used are primary data and secondary data. Primary data were obtained from direct interviews with cayenne pepper farming owners in the research destination villages. Secondary data was obtained through documentation of data that has been published by various agencies and literature related to this study. The results showed that the income of cayenne pepper farming in Tambelang Village, Maesaan District was very profitable with an income of Rp. 17,531,094 / planting season and if it is calculated per month, it is found that the average income per month has a very large income.